Scientific and technological capabilities in health-related areas: opportunities, challenges, and interactions with the industrial sector - Marco Antonio Vargas; Jorge Britto
Abstract: Characterization of the scientific and technological infrastructure in health and its interactions with the industrial sector provides key elements for understanding the dynamics of innovation in health. This study conducts an exploratory analysis of the potentialities and limitations associated with scientific and technological capabilities in the health area in Brazil and the different links between the scientific and industrial sectors in health. The analysis points to important growth in internationally indexed research output, especially in certain areas such as pharmaceutics, public health, genetics, morphology, physiology, and microbiology. There has also been important growth in research groups that interact with the industrial sector in selected areas of health. The study highlights the importance of building more solid and permanent bridges between companies, research institutions, and the health system, linking the knowledge developed in research institutions to the dynamics of the industrial sector in health.